Effect of goverment expenditure and total company to gross regional domestic product and local revenue regency/city in north kalimantan province (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
The purpose of this research is to analyze and examine : (1) The relationship and the influence of Goverment Expenditure and Total Company directly to the Gross Regional Domestic Product. (2) The relationship and the influence of Goverment Expenditure, Total Company and Gross Regional Domestic Product directly against the Local Revenue. (3) Goverment Expenditure and Total Company indirectly to Local Revenue through Gross Domestic Regional Product Regency/City in North Kalimantan Province. This research formed by secondary data for 5 years (2010-2014) gathered from various Institutions in North Kalimantan Province level, namely : (1) The Central Bureau of Statistics, (2) the Monetary Division Secretariat of the Regency/City and (3) Office Investment and Integrated Licensing Services. Statistical methods used in the study is a model of Path Analysis, with the completion of the using program SPSS for Windows Release 23.0. Result analysis and discussion is unknown if : (1) Government Expenditure is positive and significant effect directly on the Gross Regional Domestic Product. (2) Total Company is positive and significant effect directly on the Gross Regional Domestic Product. (3) Government Expenditure is positive and significant effect directly on the Local Reveneu. (4) Total Company is negative and significant effect directly on the Local Reveneu. (5) Gross Regional Domestic Product positive and significant effect on the Local Reveneu. (6) The indirectly effect of Government Expenditure on Local Reveneu through Gross Regional Domestic Product is positive and not significant. (7) The indirectly effect of Total Company on Local Reveneu through Gross Regional Domestic Product Regency/City in the North Borneo Province is positive and not significant.